Further studies of the frequency and significance of the Tgamma-chain of human fetal hemoglobin. - Schroeder, W A (1979)
A further study of the Tgamma-chain in a variety of conditions has revealed its presence in the cord bloods of ethnic groups previously unstudied. Heterozygous newborn average 17-19% Tgamma-chain while the mean value in four presumed homozygotes was 31%. The Tgamma-chain is readily detectable in beta-thalassemia of various ethnic groups (although infrequent in Blacks) as well as in deltabeta-thalassemia. Studies of a few families have provided an opportunity to determine whether or not certain individuals are heterozygous or homozygous for the Tgamma-gene. The Tgamma-chain has not been detected in the human fetal hemoglobin that is synthesized in increased amounts in persons with the hereditary persistence of fetal hemoglobin. Although the Tgamma-chain is detectable in sickle cell anemia, its frequency appears to be lower than in normal individuals. By focusing upon the relationship of the percentage of Tgamma-chain to the sources of human fetal globulin from determinants in cis and in trans, the conclusion has been reached that the Tgamma-chain is the product of a mutant Agamma-locus which should be named the TAgamma-chain.